Adaptasi Digital Communication Empathy Scale (DCES) Versi Bahasa Indonesia pada Remaja hingga Dewasa Awal - Fiandra, Khairunnisa; Rahayu Hardianti Utami (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2025)
The use of the internet to access social media often creates an echo chamber that also reinforces polarization. Continued polarization can reduce opportunities for mutual understanding and empathy towards individuals with different views. The increase in empathy during adolescence and findings that higher empathy in adolescence predicts higher empathy at age 35 necessitate the measurement of psychological empathy, particularly digital empathy, in adolescence to early adulthood. There is a theoretical possibility that digital empathy may be separate from general empathy. There have been no studies that adapt and translate digital empathy measurement tools such as the Digital Communication Empathy Scale (DCES). This study aims to determine the adaptation process of the DCES in adolescence to early adulthood and the existence of good construct validity and adequate reliability in the DCES. The subjects of this quantitative descriptive study numbered 398 participants in the Exploratory Factor Analysis (EFA) test and 403 participants in the Confirmatory Factor Analysis (CFA) test. Although the DCES has good construct validity and adequate reliability, the poor adaptation process resulted in the measurement tool not being equivalent to the original version. Therefore, this study found that only 35 of the 36 items passed the EFA test, and five of the six factors were obtained in the CFA test.